ANALYZING FACTORS THAT DRIVE CONSUMER PURCHASE DECISION OF PRODUCT AT HYPERMART MANADO - Janice, Dauhan; Saerang, David P. E; Pandowo, Merinda (FEB Universitas Sam Ratulangi Manado, 2017)
ABSTRACT: The growth of hypermarket business is enormously fast in Indonesia. Being an original Indonesian hypermarket retailer, Hypermart was able to compete with foreign retailers and become number one with its presence in more than 60 cities across the country. This research is aimed to identify the factors that drive consumer purchasing on Hypermart Manado using Factor Analysis for data reduction that summarizes the observed factors. The population observed is consumers of Hypermart Manado with 100 respondents as the sample size. The result of this study shows that good location, discount, and brand image are three most dominant out of seventeen factors tested. The recommendations for the company are to keep in mind a strategic location when opening new branches, offer discount to attract more purchases and maintain a good brand image, because these three factors are what drive consumer purchase decision in Hypermart Manado.Â Keywords: hypermarket, retail business, consumer purchase decision